Long‐term statistics of corona loss of HVDC transmission line. Issue 16 (13th February 2019) - Yu, Zhanqing; Wang, Xiaorui; Zeng, Rong; Liu, Lei; Li, Min
Abstract : Corona loss is one of the electromagnetic environment parameters of high‐voltage direct current (HVDC) transmission lines. So far many countries have carried out researches and measurements on it. In 2008, UHVDC test lines were established in the National Engineering Laboratory for UHV Technology (Kunming) at the altitude about 2100 m. The results in this study are based on the measurement data at the Kunming Experimental Base. The study mainly introduces the influence of the minimum conductor‐to‐ground height, bundle distance and pole spacing on the corona loss.